Prevalence of ERG expression and PTEN loss in a Brazilian prostate cancer cohort - Morais, C.E. (Braz J Med Biol Res, 2019)
PTEN is the most commonly inactivated tumor suppressor gene in primary prostate cancer (PCa) and its loss is associated with poor clinical outcomes. ERG rearrangement is a genomic alteration frequently found in PCa and its prognostic significance has yielded mixed results. Although the association of PTEN and ERG biomarkers has potential impact on clinical outcomes, studies examining the two genes simultaneously are scarce in Brazilian populations. In this study, we retrospectively examined the relationship between ERG expression and PTEN loss in 119 surgically treated prostate cancer patients from Northeastern Brazil through immunohistochemical analysis. ERG expression was found in 41.0% (48/117) of cases and the loss of PTEN detected in 38.1% (40/105) of samples. ERG-positive cases were significantly associated with lower prostate weight; ERG negatively correlated with Gleason score above 6. The lack of associations for PTEN loss alone in this cohort is counter to the literature, which shows that PTEN loss is usually associated with more aggressive disease. The overlapping of the two biomarkers revealed that samples with positive ERG expression without PTEN loss were associated with lower Gleason and lower Grade group. This study contributes with the discussion about the development of the molecular profiling of prostate cancer. The further development of similar studies could help in stratifying specific risk groups, leading to a more personalized therapeutic decision for prostate cancer treatment.